Ethical Consumerism and Techniques of Neutralisation in the Hybrid Electric Car Market: An Application of the Theory of Planned Behaviour - Biddle, Tom (2008)
While there is a wealth of literature investigating ethical consumerism for many consumer products (fair trade, organic), but extant literature neglects applications of the Theory of Planned Behaviour in the Hybrid Electric Vehicle (HEV) market. The dire market penetration of HEV's in the UK is currently 0.1%, with a Government target of 10% by 2012. The Theory of Planned Behaviour is applied to a young (16-25 years of age) sample (n = 180), into which preliminary exploration of techniques of Neutralisation is included. Regressional analysis finds subjective norms, self-identity and ethical obligation to be the most influential factors in HEV purchasing, while appealing to higher loyalties is the most applied technique of neutralisation. More research is needed to find a methodological way to incorporate neutralisation techniques into the Theory of Planned Behaviour. Implications and future research suggestions are discussed.